2004
DOI: 10.1177/136140960400900110
|View full text |Cite
|
Sign up to set email alerts
|

Seconding health care assistants to a pre-registration nursing course: Evaluation of a novel scheme

Abstract: Traditionally in the United Kingdom, reliance has been placed on unqualified support workers, such as student nurses, to deliver a high proportion of patient care. However, the move of nurse education into higher education and the accompanying supernumerary status of student nurses in the 1980s resulted in a shortfall of staff to deliver that care. The government has made a number of suggestions for increasing recruitment. One possible solution regarded as very promising is to encourage health care assistants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Some helped plan courses or contributed to teaching. Some universities and trusts operate programmes to enable existing HCAs to attain registration (Gould et al. 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Some helped plan courses or contributed to teaching. Some universities and trusts operate programmes to enable existing HCAs to attain registration (Gould et al. 2004).…”
Section: Resultsmentioning
confidence: 99%
“…As indicated in the comments above, the secondees made full use of the university academic support services. The earlier evaluation had indicated that they had also received a great deal of support from their personal tutor (Gould et al, 2004). In contrast, the secondees coped well in their clinical placements compared to traditional students, especially during the 18-month common foundation programme:…”
Section: Resultsmentioning
confidence: 99%
“…The findings from a major acute London trust which has been operating the scheme since 1999 have indicated that secondees and other stakeholders are satisfied with the scheme (Gould et al, 2004). However, only a small number of eligible HCAs have been willing to undergo secondment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCSWs often provide a great deal of the day‐to‐day support for children with complex and continuing health needs (Hewitt‐Taylor, 2004). Their precise role in health care varies according to the organization for which they work and their level of training and experience; but a considerable amount of nursing care in England is carried out by HCSWs in both hospital and community settings (Gould, Carr, Kelly, & Brown, 2004; Ormandy, Long, Hulme, & Johnson, 2004; Spilsbury & Meyer, 2004). HCSWs working with Clinovia complete a formal induction and training program and are assessed against competencies in all the areas in which they provide support.…”
Section: The Pilot Placementmentioning
confidence: 99%